New Technologies and the Law of Armed Conflict
XX, 259 p. 1 illus.
Keywords: With a Foreword by Michael N. Schmitt, Charles H. Stockton Professor and Chairman, United States Naval War College. Modern technological development has been both rapid and fundamentally transformative of the means and methods of warfare, and of the broader environment in which warfare is conducted. In many cases, technological development has been stimulated by, and dedicated to, addressing military requirements. On other occasions, technological developments outside the military sphere affect or inform the conduct of warfare and military expectations. The introduction of new technologies such as information technology, space technologies, nanotechnology and robotic technologies into our civil life, and into warfare, is expected to influence the application and interpretation of the existing rules of the law of armed conflict. In this book, scholars and practitioners working in the fields critically examine the potential legal challenges arising from the use of new technologies and future directions of legal development in light of the specific characteristics and challenges each technology presents with regard to foreseeable humanitarian impacts upon the battlespace. New Technologies and the Law of Armed Conflict is highly recommended to everyone involved in the ongoing weapons debates, as well as those interested in the broader relationship between law and war. Hitoshi Nasu and Robert McLaughlin are Senior Lecturer and Associate Professor respectively at the ANU College of Law, AustralianNational University, Canberra ACT, Australia.